Clinical, radiographic, biochemical and histological findings of florid cemento-osseous dysplasia and report of a case - Gonçalves, Marcelo [UNESP]; Píspico, Ronaldo; Alves, Fábio de Abreu; Lugão, Carlos Eduardo B. [UNESP]; Gonçalves, Andréa [UNESP] (Fundação Odontológica de Ribeirão Preto, 2005)
A displasia cemento-óssea florida tem sido descrita como uma condição que afeta tipicamente os maxilares de mulheres negras de meia idade. Ela geralmente se manifesta como múltiplas massas radiopacas semelhantes ao cemento distribuídas nos maxilares. Esta condição também tem sido classificada por vários autores como cementoma gigantiforme, osteomielite esclerosante crônica, osteíte esclerosante e massas de cemento escleróticas. Os autores apresentam um caso de displasia cemento-óssea florida não complicada em uma mulher negra de 48 anos de idade. Múltiplas massas escleróticas com bordas radiolúcidas na mandíbula foram identificadas radiograficamente. Os achados histopatológicos revelaram formação de massas escleróticas densas calcificadas semelhantes ao cemento. Todos os aspectos clínicos, radiográficos, bioquímicos e histológicos foram sugestivos do diagnóstico de displasia cemento-óssea florida.

Florid cemento-osseous dysplasia has been described as a condition that characteristically affects the jaws of middle-aged black women. It usually manifests as multiple radiopaque cementum-like masses distributed throughout the jaws. This condition has also been classified as gigantiform cementoma, chronic sclerosing osteomyelitis, sclerosing osteitis, multiple estenosis and sclerotic cemental masses. The authors present a case of an uncomplicated florid cemento-osseous dysplasia in a 48-year-old black woman. Multiple sclerotic masses with radiolucent border in the mandible were identified radiographically. Histopathologic findings revealed formation of calcified dense sclerotic masses similar to cementum. All clinical, radiographic, biochemical and histological features were suggestive of the diagnosis of florid cemento-osseous dysplasia.
Keywords: florid cemento-osseous dysplasia; florid osseous dysplasia; fibro-osseous lesions